Suicidal hanging in Manipal (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Hanging is one of the most commonly used methods for suicide worldwide. A retrospective autopsy study of suicidal hanging was undertaken in the Department of Forensic Medicine, Kasturba Medical College, Manipal, South India, over a period of 15 years (1992 to 2007). Suicidal hanging constituted 3.5% of the total autopsied unnatural deaths at our mortuary. Adults in the third decade of life and male sex predominated. Deaths occurred more during the day time and in the winter months. Psychological stress in life was the most common motive respon sible for committing suicide.
Keywords: Fatality; hanging; suicide